(untitled) (Research, Society and Development, 2026)
Objective: To describe the clinical and epidemiological profile and outcome of pediatric patients aged 29 days to under 13 years admitted to the intensive care unit of HUMAP/EBSERH due to respiratory infections. Methodology: This was a cross-sectional, retrospective study with a quantitative approach using data from patients aged 29 days to under 13 years admitted to the intensive care unit of HUMAP/EBSERH between January 1, 2023, and December 31, 2024. Data obtained from the "Pediatric ICU Admission" control spreadsheets and epidemiological data from the Epidemiology sector of HUMAP/EBSERH were used. Results: Of the 158 patients admitted to the pediatric ICU, 89 (54.27%) were female and 75 (45.73%) were male. The main cause of admissions was respiratory diseases, with bronchiolitis being the most common (20.4%). Infants accounted for the largest number of admissions (61.4%) and presented greater severity, requiring mechanical ventilation in 32.3% of cases. Patients with flu-like symptoms underwent viral panel testing for pathogen identification, and the main viral agent identified was respiratory syncytial virus. Conclusion: Respiratory diseases continue to have a significant impact on children’s health. Preventive measures for respiratory infections are increasingly important, as are investments in supportive treatments and management to ensure better case outcomes and consequently reduce hospitalization costs.